Soil organic carbon in cropping sequences with predominance of soya bean in the argentinean humid Pampas - Martinez, Juan Pablo; Crespo, Cecilia; Sainz Rozas, Hernan Rene; Echeverria, Hernan Eduardo; Studdert, Guillermo; Martinez, Fernando Gabriel; Cordone, Graciela; Barbieri, Pablo (Wiley, 2022)
Soya bean (Glycine max (L.) Merr.) monoculture can lead to a decrease in labile fractions of soil organic carbon (SOC). This study sought to evaluate the effects of cover crops (CC), application of fertilizer, and crop rotation on SOC, particulate organic carbon (POC), and soil carbon input in soya bean-based crop sequences under a no-till cropping system in the Argentinean Humid Pampas. Five crop sequences at two sites differing in initial SOC were evaluated: continuous soya bean (Sb), continuous soya bean fertilized with phosphorus (P) and sulphur (S) (Sbf), grass CC / PS-fertilized soya bean (CC/Sbf), nitrogen (N)-fertilized CC / PS-fertilized soya bean (CCf/Sbf) and NPS-fertilized crop rotation with high intensification sequence index (ISI) (Rot). At 0–5 cm, SOC and POC were higher (p < .05) in the sequences with higher residue-C supply (CC/Sbf; CCf/Sbf and Rot) at both sites. Changes in SOC at 0–20 cm simulated by AMG model closely tracked measured results at 0–20 cm. Findings from this study suggest that the inclusion of CC or crop rotation with high ISI improved C balance in soils under crop sequences with soya bean predominance.